Mathematical model of a root harvester after-cleaning system - Hevko, R.B.; Tkachenko, I.G.; Hlado, Y.B.; Synii, S.V.; Gandziuk, M.O.; Trokhaniak, O.M. (Bulletin of the Karaganda University. Mathematics Series, 2019)
A mathematical model of root crops after cleaning and their movement pattern in a technological run for loading into means of transportation has been presented. The impact of both controlled and uncontrolled factors on the eﬃcient continuous transportation of root crops has been determined on the basis of the above mentioned model. The use of the suggested mathematical model will enable to narrow the search of the most eﬃcient design, kinematic and dynamic parameters in conducting some experimental research on eﬃcient operation of after cleaning systems of harvesters with their possible adjustment according to the natural and climatic conditions of harvesting.